Prinsip Hidup yang Mengingat Tuhan: Studi Hermeneutik terhadap Yakobus 4:13-17 - Otniel Aurelius Nole (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
Human have the ability to remember in life, which as a system called memory. Human can also experience forgetfulness as James 4:13-17 explains the activities and life plans of traders. The purpose of this article was to investigate the principles of living by remembering God based on James 4:13-17. The researcher used a qualitative method with a hermeneutic study viewed from a psycho-theological perspective. The researcher found that the life of the traders was reflecting self-aggrandizement with arrogance and forgetting God. Apart from admonishing them, James gave advice to practice the principles of life that remember God. In this case, individuals need to apply memory improvement strategies about remembering God constantly, namely activating spiritual learning, diligent communication, and high interest. Thus, individuals know the truth and implement good deeds.